EVALUASI KEBIJAKAN PEMBANGUNAN IRIGASI DALAM INTENSIFIKASI PRODUKTIFITAS SAWAH DI DESA SAWAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Nita Febriani; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This paper was aimed at finding out the effectiveness of the implementation irrigation development towards the intensification of rice fields’ productivity and analyzing the factors that influence the effectiveness of the implementation. The research was conducted in the Middle District of Kuantan District Singingi. This research was conducted in the Central District of Kuantan District Singingi from September to November 2013. The data collected through interview and observation and analyzed by using qualitative descriptive analysis. The findings of this research showed that the effectiveness of the implementation of irrigation development towards the intensification of the rice fields’ productivity was very effective. The finding also showed that the dominant factors influenced the effectiveness of the implementation irrigation development towards the intensification of rice fields’ productivity were the factors of the human resources, capital and water resources.Keywords: Effectiveness, Development Towards, Irrigation